2008
DOI: 10.1002/syn.20540
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and ultradian rhythms in the crayfish caudal photoreceptor

Abstract: The study of circadian clocks in crustaceans has led to the hypothesis of a distributed circadian system of pacemakers. In this review, we investigate the role of the crayfish caudal photoreceptor (CPR) as a candidate to form part of this pacemaking circadian system. Two circadian rhythms are documented for CPR electrical activity. These rhythms correspond to the spontaneous and light-induced discharge of action potentials. The intrinsic characterization of the rhythms is made through the analysis of the firin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…This has been interpreted as a result of circadian changes in the sensitivity of the CPR. Thus, the CPR shows circadian rhythms in activity as well as in sensitivity, the latter being comparable to the intrinsic rhythmicity characteristic for the retinal ERG (12). It is intriguing that both the light sensitivity and the circadian activity reside in the same oscillator neuron.…”
Section: The Caudal Photoreceptor Of the Crayfish Terminal Abdominal mentioning
confidence: 71%
See 2 more Smart Citations
“…This has been interpreted as a result of circadian changes in the sensitivity of the CPR. Thus, the CPR shows circadian rhythms in activity as well as in sensitivity, the latter being comparable to the intrinsic rhythmicity characteristic for the retinal ERG (12). It is intriguing that both the light sensitivity and the circadian activity reside in the same oscillator neuron.…”
Section: The Caudal Photoreceptor Of the Crayfish Terminal Abdominal mentioning
confidence: 71%
“…Whilst ultradian rhythms have been detected in many systems (12), their functional significance has yet to be determined. They are often excluded from further analyses (23), which may well leave aspects of great biological importance unrecognised.…”
Section: Chronobiological Systems In Crustaceamentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated by chronic EMG recording that the locomotor behavior was initiated spontaneously, not reflexively by any external stimulus. It has been proposed that the locomotory circadian rhythmicity of P. clarkii is generated by clock proteins and regulated by hormonal and neuromodulator secretion in the brain [3,41,43] and also is regulated by photoreceptors in the brain [37,38,43] or in the 6 th abdominal ganglion [56,57]. Although the details of interaction cascades among those factors remain unknown, the brain should play an important role for the circadian locomotor activity [3,38,43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using Procambarus bouvieri showed that there was a correlation between the rhythms of ERG and locomotor activity in intact and brainless crayfish [27], and that its caudal photoreceptors functioned as a circadian photoreceptor [55]. Recent research using Procambarus clarkii and Cherax quadricarinatus suggests that the caudal photoreceptor contributes to the entrainment of circadian locomotor activity [56,57]. Meanwhile, other studies using P. clarkii demonstrated that the brain photoreceptors are necessary for the entrainment of locomotor activity rhythms to light stimuli [38], and that they can function in the absence of the compound eyes and caudal photoreceptors [37,43].…”
Section: Effects Of Retinal and Extraretinal Input On The Circadian Rmentioning
confidence: 99%